2009
DOI: 10.1007/s11671-009-9279-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled 3D Flower-Like Hierarchical β-Ni(OH)2Hollow Architectures and their In Situ Thermal Conversion to NiO

Abstract: Three-dimensional (3D) flower-like hierarchicalβ-Ni(OH)2hollow architectures were synthesized by a facile hydrothermal route. The as-obtained products were well characterized by XRD, SEM, TEM (HRTEM), SAED, and DSC-TGA. It was shown that the 3D flower-like hierarchicalβ-Ni(OH)2hollow architectures with a diameter of several micrometers are assembled from nanosheets with a thickness of 10–20 nm and a width of 0.5–2.5 μm. A rational mechanism of formation was proposed on the basis of a range of contrasting exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 41 publications
3
41
1
Order By: Relevance
“…Then a secondary nucleation would be favored, and cubic angular protuberances would grow into nanopetals combining with the remaining primary particles, finally forming the 3D flower-like hierarchitectures, a process which is similar to that described as "the terrace-step-kink model" [27]. This is similar to the formation process of those flower-like nanocrystals reported previously, such as CoS [28], CuO [29], TiS 2 [30], In 2 O 3 [31], AlO(OH) [32], ZnO [33], Bi 2 MoO 6 [34], Ni(OH) 2 [35] and so on.…”
Section: Growth Mechanism Of In 2 S 3 Nanoflowerssupporting
confidence: 79%
“…Then a secondary nucleation would be favored, and cubic angular protuberances would grow into nanopetals combining with the remaining primary particles, finally forming the 3D flower-like hierarchitectures, a process which is similar to that described as "the terrace-step-kink model" [27]. This is similar to the formation process of those flower-like nanocrystals reported previously, such as CoS [28], CuO [29], TiS 2 [30], In 2 O 3 [31], AlO(OH) [32], ZnO [33], Bi 2 MoO 6 [34], Ni(OH) 2 [35] and so on.…”
Section: Growth Mechanism Of In 2 S 3 Nanoflowerssupporting
confidence: 79%
“…Then, a secondary nucleation is favorable, and cubic angular protuberances grow into nanopetals combining with the remaining primary particles, finally forming the 3D flower-like hierarchitecture, which is similar to what has been described as the terrace-step-kink model [23]. This is similar to the formation process of the flowerlike nanocrystals, such as CoS [24], CuO [25], TiS 2 [26], In 2 O 3 [27], AlOOH [28], Bi 2 MoO 6 [29], Ni(OH) 2 [30] reported previously. The photocatalytic activity of the as-prepared ZnO samples was evaluated by degradation of MB dye under UV-A light irradiation.…”
Section: Effects Of Solution Ph On the Morphology Of Zno Crystalsmentioning
confidence: 62%
“…Previous works in the literature observed that as a consequence of the nickel presence, the particle size decreases and thus, the amount of crystalline facets [31]. Moreover, the presence of crystalline -Ni(OH)2 was evidenced from the peak located at ~20º, which corresponds to the reflection of the (001) facet for this specie [32]. In the case of the materials supported on CNFs, an intense peak close to 25º was observed, which corresponds to the C(002) graphite basal planes [33,34].…”
Section: Physical Characterizationmentioning
confidence: 69%